Associations of Bone Mineral Density with Lean Mass, Fat Mass, and Dietary Patterns in Postmenopausal Chinese Women: A 2-Year Prospective Study - Yongjie, Chen (Public Library of Science (PLoS), 2018)
To assess factors associated with bone mineral density (BMD) in postmenopausal women in a longitudinal study, and to examine the relative contribution of lean mass, fat mass, dietary patterns, and years since menopause to BMD.Two hundred and eighty-two postmenopausal women were randomly selected from Hongqi Community Health Center, in Harbin City, China. All participants were followed up from 2009 to 2011. Dietary data were collected using a Food Frequency Questionnaire. BMD of the left hip, the lumbar spine, and the total body, and the body composition were measured by dual-energy X-ray absorptiometry at baseline and follow-up.Lean mass and fat mass were positively associated with BMD of the spine, hip, and the total body at both baseline and follow-up. The association between fat mass and BMD at the spine at baseline (P = 0.210) and at the spine (P = 0.116) and hip (P = 0.073) in the second year was not statistically significant when height was adjusted. Six dietary patterns were identified but only cereal grains-fruits pattern (P = 0.001 in the spine, P = 0.037 in hip) and milk-root vegetables pattern (P = 0.010 in hip) were associated with BMD of the spine and hip. The linear mixed model of follow-up data showed that lean mass, years since menopause, and age of menophania were the significant determinants of BMD of all sites. Moreover, lean mass was the best determinant of BMD (VIP = 1.936).Lean mass, years since menopause, age of menophania and dietary patterns are the important determinants of BMD of the spine, hip, and the total body. Lean mass is the best determinant of BMD.